Levetiracetam modulates brain metabolic networks and transcriptomic signatures in the 5XFAD mouse model of Alzheimer’s disease - Burton, Charles P.; Chumin, Evgeny J.; Collins, Alyssa Y.; Persohn, Scott A.; Onos, Kristen D.; Pandey, Ravi S.; Quinney, Sara K.; Territo, Paul R. (Frontiers in Neuroscience, 2024)
is an FDA approved anti-convulsant and is currently under clinical trials in AD patients. In this manuscript, Burton et al. studied brain metabolic networks and transcriptomic signatures in 5XFAD mice after the treatment of LEV. It was found that there were significant dose-dependent changes in region-wise glycolytic correlation and gene expression changes in response to LEV. Overall, this study is novel and interesting, providing translational value towards informing clinical study design.Comments: 1. In Methods section, it was stated that LEV was given via oral gavage for chronic studies in 5xFAD mice, but there is no information on administration route in LEV PK studies.